Public elements of the legal status of the things on which the mode of immobile thing is widespread - Нікітіна, Зоя Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article describes the elements of public and legal status of things on which the mode of immobile thing is widespread. The author also studies public elements of the legal status of the immobilized things. State registration of things defined as administrative activities, which is closely associated with other forms of administration. An object of research is the legal status of the things on which the mode of immobile thing is widespread. The aim of the article consists of definition of the legal nature of public law elements of the legal status of mentioned things. The results of the article can be used in further research of distribution of the mode of immobile thing.